Study of J-E Curve with Hysteresis of Carbon Nanotubes Field Emitters. (16th August 2012) - Parveen, Shama; Husain, Samina; Kumar, Avshish; Ali, Javid; Harsh,; Husain, Mushahid
Abstract : We observe hysteresis in J-E plot during field emission measurement of CNTs grown by LPCVD technique. CNTs are synthesized on Fe-coated Si substrate at 650°C. SEM and Raman study confirm that CNTs are successfully grown on Si substrate by LPCVD technique. In this study, we find that ramp-down curve has higher value of current density than ramp-up curve which indicates that CNTs show positive hysteresis. Our results show that a high current density at low turn-on voltage is obtained in ramp-down step of J-E plot which may be since not all CNTs contribute in ramp-up step process. But in ramp-down step all CNTs contribute as field emitters due to high electric field treatment. We also performed stability analysis of CNTs with current at constant applied voltage for 5 hrs and find that the sample shows long-term stability due to increase in emitting site density since a large number of CNTs participate in field emission.